Transmission of Helicobacter pylori Infection. (1st September 1999) - Oderda, Giuseppina
Abstract : Helicobacter pylori infection is one of the most common bacterial infections worldwide. It is accepted as the major cause of chronic gastritis, peptic ulcer, carcinoma of the distal part of the stomach and gastric lymphoma. However, how and when the infection is acquired remain largely unknown. Identification of mode of transmission is vital for developing preventive measures to interrupt its spread, but studies focused on this issue are difficult to implement. From epidemiological studies, it is known that there are great differences in the prevalence of infection in different populations and in ethnic groups originating from high prevalence regions. This is likely related to inferior hygienic conditions and sanitation. In developing countries, infection occurs at a much earlier age. In developed countries, the prevalence of infection is related to poor socioeconomic conditions, particularly density of living. Humans seem to be the only reservoir of H pylori, which spread from person to person by oral-oral, fecal-oral or gastro-oral routes. Most infections are acquired in childhood, possibly from parents or other children living as close contacts. Infection from the environment or from animals cannot be entirely excluded.